MANAGEMENT OF GRADE II HYPERTENSION WITH HISTORY OF NON HEMORAGIC STROKE - Edmi, Febriyan (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Hypertension and stroke is very common disease. The prevalence of hypertensiom continues to increase compared to previous years throughout the world and in Indonesia. Application of family medicine services based on Evidence Based Medicine (EBM) in patients with identified risk factors, clinical problems, as well as the management of the patient based on the framework of problem settlement with patient centre and family approaches. This study is a case report. The primary data obtained through allonamnesis (patient husband), physical examination, household and family circumstances. Based on a holistic assessment of the initial diagnosis. Assessment of study was quantitative and qualitative. Male, 47 years old, with hypertension grade II and history of stroke non hemorrhagic 3 months ago. Risk factors was identified, blood pressure was checked, and furthermore, given the pharmacological and nonpharmacological management. Internal risk factors are elderly, patient’s parent had a hypertension history, treatment patterns still priority on curative, lack of knowledge about the illness, lack of knowledge about diet for people with hypertension and stroke, lack of knowledge about the importance of regular exercise. Patient then Provided with education about the disease and the importance of improving diet in accordance with the disease and post stroke rehabilitation. Result obtained improvement, blood pressure was controlled and patient knowledge about the disease and healthy lifestyle are increases. The role of the family was very important in the shared responsibility of complications and preventive measures. [J Agromed Unila 2014; 1(2):170-173] Keywords: hypertension, non hemoragic stroke